Urban and Regional Planning and Development. 20th Century Forms and 21st Century Transformations. - (:unkn) unknown (My University, 2020)
The book discusses urban planning and regional development practices in the twentieth century, and ways in which they are currently being transformed. It addresses questions such as: What are the factors affecting planning dynamics at local, regional, national and global scales? With the push to adopt a market paradigm in land development and infrastructure, the relationship between resource management, sustainable development and the role of governance has been transformed. Centralized planning is giving way to privatization, not only in the traditional regions but also in newly emerging regions of Asia, Africa and Latin America. Further, attempts are being made to bring planning related decision-making closer to the people who are most affected by it. Presenting a collection of studies from scholars around the world and highlighting recent advances in the field, the book is a valuable reference guide for those engaged in urban transformations, whether as graduate students, researchers, practitioners or policymakers
Keywords: Stadtplanung; Regionalplanung; Regionalentwicklung; Transformation; Internationaler Vergleich; Industrieland; Entwicklungsland; Schwellenland; Planungspraxis; Planungstheorie; Raumplanung; Raumentwicklung; Segregation; Soziale Ungleichheit; Flächennutzung; Urbaner Raum; Suburbaner Raum; Öffentlicher Raum; Öffentliche Sicherheit; Urban Governance; Dezentralisation; Nachhaltige Stadtentwicklung